TREATMENT OF ADDITION OF SELENOMETIONIN IN FEED FOR GROWTH AND RESISTANCE OF JUVENIL BODY CANTANG FISH (Epinephelus fuscoguttatus x Epinephelus lanceolatus) - Gitra - Yoga; David Hermawan; Riza Rahman Hakim (Universitas Muhammadiyah Malang, 2024)
Cantang grouper is a superior marine aquaculture commodity with high economic value; however, disease susceptibility and suboptimal growth remain major challenges in its culture. Selenium in the form of selenomethionine (Se) is known to function as an antioxidant and immunostimulant that may improve fish growth and health performance. Therefore, this study aimed to evaluate the effect of dietary selenomethionine supplementation on the growth, hematocrit levels, and phagocytic activity of Cantang grouper. This study employed an experimental method using a Completely Randomized Design (CRD) with five treatments and three replications. The treatments consisted of different Se supplementation levels in feed, namely 0 mg/kg (control), 4 mg/kg, 8 mg/kg, 12 mg/kg, and 16 mg/kg feed. Cantang grouper with an initial size of 8 cm and an average weight of 12.95 g were used as experimental fish. Parameters observed included growth performance, hematocrit levels after challenge with Vibrio vulnificus, and phagocytic activity following challenge with Staphylococcus aureus at 10⁷ CFU/mL. The results showed that selenomethionine supplementation significantly affected fish growth and immune response. The best performance was obtained in treatment E (16 mg Se/kg feed), which produced the highest final length (11.82 cm) and weight (26.63 g). The same treatment also resulted in the highest hematocrit value (27.59%) and phagocytic activity (37.09%). In conclusion, dietary supplementation of 16 mg Se/kg feed effectively enhanced growth and immune responses of Cantang grouper, indicating its potential application in improving aquaculture productivity and disease resistance.